UPAYA MENINGKATKAN HASIL PEMBELAJARAN IPS MELALUI PENERAPAN MODEL GRUP INVESTIGATION SISWA KELAS V SDN 1 TALANG TELUK BETUNG SELATAN BANDAR LAMPUNG - Helnawati, Helnawati (LPPM STKIP PGRI Bandar Lampung, 2020)
The problem raised in this study is how to improve social studies learning outcomes through the Group Investigation learning model in class V SDN 1 Talang Teluk Betung Selatan Bandar Lampung for the 2018/2019 academic year. : How is the application of the Group Investigation model so as to improve the quality of social studies learning at SDN 1 Talang Teluk Betung Selatan Bandar Lampung? The problem solving in this research is to use the Group Investigation learning model. The purpose of this study was to improve the quality of social studies learning through the Group Investigation model in class V SDN 1 Talang Teluk Betung Selatan Bandar Lampung. To achieve the research objectives mentioned above, the author uses the research method